2010
DOI: 10.1088/0004-637x/715/1/310
|View full text |Cite
|
Sign up to set email alerts
|

The Early Stages of Star Formation in Infrared Dark Clouds: Characterizing the Core Dust Properties

Abstract: Identified as extinction features against the bright Galactic mid-infrared background, infrared dark clouds (IRDCs) are thought to harbor the very earliest stages of star and cluster formation. In order to better characterize the properties of their embedded cores, we have obtained new 24 µm, 60-100 µm, and submillimeter continuum data toward a sample of 38 IRDCs. The 24 µm Spitzer images reveal that while the IRDCs remain dark, many of the cores are associated with bright 24 µm emission sources, which suggest… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
161
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(173 citation statements)
references
References 40 publications
12
161
0
Order By: Relevance
“…Wang et al (2008) reported a luminosity of 10 2 L for the 24 μm source associated with SMA2. Rathborne et al (2010) obtained a luminosity of 2.1 × 10 3 L for the entire P1 clump. These luminosities set a limit on the mass of the embedded stars of 3-7 M , if they are at the zero-age main sequence.…”
Section: Massive Star Formation Through An Intermediate-mass Stagementioning
confidence: 96%
See 1 more Smart Citation
“…Wang et al (2008) reported a luminosity of 10 2 L for the 24 μm source associated with SMA2. Rathborne et al (2010) obtained a luminosity of 2.1 × 10 3 L for the entire P1 clump. These luminosities set a limit on the mass of the embedded stars of 3-7 M , if they are at the zero-age main sequence.…”
Section: Massive Star Formation Through An Intermediate-mass Stagementioning
confidence: 96%
“…For dust in the interstellar medium, β = 2 (Draine & Lee 1984). Rathborne et al (2010) derived β = 1.5 ± 0.3 for the entire P1 clump based on a global spectral energy distribution. We generated a dust opacity map by comparing the continuum image at 345 GHz and 230 GHz, and found β to vary from 1.3 to 2.5 across the map.…”
Section: Hierarchical Fragmentationmentioning
confidence: 99%
“…(b) This is the strongest hf component and it is blended with the J, F = 7/2, 5/2−5/2, 3/2 and J, F = 7/2, 7/2−5/2, 5/2 hf components. For three of our sources, G015.05 MM1, I18223 MM3, and J18364 SMM1, dust temperature estimates have been made by Rathborne et al (2010), Beuther et al (2010), and Birkmann et al (2006), respectively. The determined dust temperature values of G015.05 MM1, 11.0-36.0 K, bracket the T kin value of 17.2 K. A dust temperature of I18223 MM3 was also derived by Beuther & Steinacker (2007) from the source SED using the Spitzer/MIPS data at 24 and 70 μm, and MAMBO 1.2 mm and PdBI 3.2 mm data.…”
Section: Kinematic Distancesmentioning
confidence: 99%
“…Such small β is often attributed to grain growth in a high-density environment (Miyake & Nakagawa 1993) and is not valid in the outer region. To convert the JCMT measurements, we adopt β = 1.6 for active protostellar cores (Rathborne et al 2010). In Figure 3(b), the polarization percentage shows a similar dependence with the beam averaged column density between the two populations of polarization measurements (Figure 3(b)).…”
Section: Comparison With Polarization Measurements On Large Scalesmentioning
confidence: 99%